Investigating sex differences in developmental origins of adolescent depression - Braithwaite, Elizabeth C.; Hargreaves, Esther; Hill, Jonathan; Pickles, Andrew; Sharp, Helen; Wright, Nicky (Frontiers in Child and Adolescent Psychiatry, 2025)
IntroductionEvolutionary hypotheses propose that fetuses show “predictive adaptive” responses to the prenatal environment based on likely continuity with the postnatal environment, and males and females have different adaptive priorities. Female adaptations appear to implicate hypothalamic-pituitary-adrenal (HPA) axis mechanisms moderated by early tactile stimulation. Based on these hypotheses we predict that lack of prenatal-postnatal environmental continuity (mismatch), will be associated with poorer outcomes in females, an effect that will be ameliorated by tactile stimulation. We previously reported that this prediction was supported by evidence from the Wirral Child Health and Development Study (WCHADS) of a three-way interaction between maternal prenatal anxiety, postnatal anxiety, and infant stroking in the prediction of irritability at age 7 years, seen only in girls. Here, we ask whether this effect persists over another 6 years into early adolescence.MethodsMothers in a general population cohort (WCHADS) provided self-reported anxiety scores at 20 weeks of pregnancy, and at 9 weeks, 14 months and 3.5 years postpartum, and frequency of infant stroking at 9 weeks. Their children self-reported symptoms of depression in early adolescence at age 13 years. Structural equation modelling (SEM) with maximum-likelihood estimation was conducted using data from N = 695 mother-child dyads.ResultsThere was a three-way interaction between prenatal and postnatal anxiety and maternal stroking in the prediction of early adolescent depression, seen only in girls, consistent with our previous reports. When examining self-reported depression at age 13 years, increased stroking was associated with decreased symptoms of depression in girls in the mis-match group characterised by low prenatal and high postal anxiety, but not the high prenatal and low postnatal mis-match group.DiscussionWe provide preliminary novel evidence that mechanisms likely to have evolved well before the emergence of humans, contribute to the risk of adolescent depression in girls. These findings have implications for understanding developmental origins of sex differences in adolescent depression.